2010
DOI: 10.4028/www.scientific.net/amr.146-147.619
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Cinnamon Essential Oil by β-Cyclodextrin and its Release Characteristics at High Temperature

Abstract: The high instability is one of the most important problems for cinnamon oil. The complexation of cinnamon oil by β-cyclodextrin (β-CD) and its controlled release characteristics were investigated in this paper. The composition of microencapsulated cinnamon oil was evaluated using Fourier transform infrared spectroscopy (FT-IR). The size distribution and surface morphology of the resultant microcapsules were also characterized using Beckman Coulter particle size analysis, scanning electron microscopy (SEM), res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In addition to common microencapsulation techniques explained above, there are limited oil encapsulation studies including single layer emulsions [164,165]; multilayer emulsions [166,167]; molecular inclusion [168][169][170]; use of particles from gassaturated solution (PGSS) process [171]; use of macroscopic beads [172] and miniemulsification-solvent evaporation technique [173]. In particular, new and expensive methods are evaluated to preserve volatile compounds of essential oils.…”
Section: Other Methodsmentioning
confidence: 99%
“…In addition to common microencapsulation techniques explained above, there are limited oil encapsulation studies including single layer emulsions [164,165]; multilayer emulsions [166,167]; molecular inclusion [168][169][170]; use of particles from gassaturated solution (PGSS) process [171]; use of macroscopic beads [172] and miniemulsification-solvent evaporation technique [173]. In particular, new and expensive methods are evaluated to preserve volatile compounds of essential oils.…”
Section: Other Methodsmentioning
confidence: 99%
“…Many studies on the physical and chemical methods to control release in such a system have been conducted. Changes in temperature [14], pressure, and ultrasonic intensity [15] can control the release of molecules from the CD complex. The studies [16,17] published thus far suggested that modification of CD was very valuable in changing the rate of drug release.…”
Section: Introductionmentioning
confidence: 99%
“…Then the resulting slurry was dried in the air dry oven for 48 h.Finally,it was pulverized after dried. Morphology of microencapsulation [6].The shape and surface characteristics of the microencapsules were examined using a scanning electron microscope at required magnifications with the secondary electron image (SEI) as a detector and an accelerated voltage of 14 kV.Put the conductive adhesive in SEM sample table and the microencapsule powder was spread on the double-sided adhesive. Then sprayed gold with vacuum-pumping.The microencapsules were magnified 500 and 200 times.…”
Section: Introductionmentioning
confidence: 99%